Use of Mineral Weathering Bacteria to Enhance Nutrient Availability in Crops: A Review - Ribeiro, Igor Daniel Alves; Volpiano, Camila Gazolla; Vargas, Luciano Kayser; Granada, Camille Eichelberger; Lisboa, Bruno Brito; Passaglia, Luciane Maria Pereira (Frontiers in Plant Science, 2020)
Rock powders are low-cost potential sources of most of the nutrients required by higher plants for growth and development. However, slow dissolution rates of minerals represent an obstacle to the widespread use of rock powders in agriculture. Rhizosphere processes and biological weathering may further enhance mineral dissolution since the interaction between minerals, plants, and bacteria results in the release of macro- and micronutrients into the soil solution. Plants are important agents in this process acting directly in the mineral dissolution or sustaining a wide diversity of weathering microorganisms in the root environment. Meanwhile, root microorganisms promote mineral dissolution by producing complexing ligands (siderophores and organic acids), affecting the pH (via organic or inorganic acid production), or performing redox reactions. Besides that, a wide variety of rhizosphere bacteria and fungi could also promote plant development directly, synergistically contributing to the weathering activity performed by plants. The inoculation of weathering bacteria in soil or plants, especially combined with the use of crushed rocks, can increase soil fertility and improve crop production. This approach is more sustainable than conventional fertilization practices, which may contribute to reducing climate change linked to agricultural activity. Besides, it could decrease the dependency of developing countries on imported fertilizers, thus improving local development.